Germline and somatic genetic alterations in two first‐degree relatives with appendiceal low‐grade mucinous carcinoma peritonei. Issue 12 (29th September 2020) - King, Mary Caitlin; Munoz‐Zuluaga, Carlos; Ledakis, Panayotis; Studeman, Kimberley; Sittig, Michelle; Gushchin, Vadim; Sardi, Armando
Abstract: Comparing genetic mutations of first‐degree relatives with appendiceal pseudomyxoma peritonei may explain clinical outcomes and disease pathogenesis. Molecular profiling of mucinous tumors may identify improved treatments to traditional chemotherapy. Abstract : Comparing genetic mutations of first‐degree relatives with appendiceal pseudomyxoma peritonei may explain clinical outcomes and disease pathogenesis. Molecular profiling of mucinous tumors may identify improved treatments to traditional chemotherapy.